Strategi Guru Pendidikan Agama Islam dalam Meningkatkan Motivasi Belajar PAI di SD Negeri Pasir Jaya 1 Tangerang - Abdul Azis; Sutarjo Sutarjo; Lilis Karyawati (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2022)
A teacher has a great responsibility in the teaching and learning process. Therefore, teachers must motivate students because motivation is a factor that can influence the success or failure of all student activities in learning. This study aims to determine the Islamic Religious Education teacher's strategy in increasing learning motivation, the Islamic Religious Education teacher's efforts to increase student learning motivation and to find out the obstacles and solutions as an Islamic Religious Education teacher's effort to increase motivation in SD Negri Pasir Jaya 1 Tangerang. This research method uses a qualitative approach with data collection techniques through observation, interviews and documentation studies. The results of the study concluded that the PAI teacher's strategy in improving motivational student learning outcomes at the Negri Elementary School in Pasir Jaya 1 Tangerang Regency can be carried out in several steps, including: explaining learning objectives to students, giving prizes (award), raising competition or competence, giving praise, giving punishments and sanctions, arousing enthusiasm for learning, forming good study habits, helping students with learning difficulties both individually and in groups, using various methods and must be in accordance with learning objectives.